Delayed Tibial Osteomyelitis after Anterior Cruciate Ligament Reconstruction with Hamstrings Autograft and Bioabsorbable Interference Screw: A Case Report and Review of the Literature - Kevin S. Weiss; Justin M. Weatherall; Jen Eick; James R. Ross (Case Reports in Orthopedics)
Osteomyelitis following arthroscopically assisted anterior cruciate ligament (ACL) reconstruction has rarely been reported in the literature. We report a case of a 20-year-old female who had delayed tibial osteomyelitis and a pretibial cyst with culture-positive, oxacillin sensitive Staphylococcus epidermidis 15 months after an ACL reconstruction with hamstring autograft. Soft tissue fixation within the tibial tunnel was with a poly-L-D-lactic acid (PLDLA) bioabsorbable interference screw. The patient underwent surgical treatment with curettage, debridement, hardware removal, and bone grafting of the tibial tunnel followed by a course of intravenous antibiotics. Arthroscopic evaluation demonstrated an intact ACL graft without any evidence of intra-articular infection. The patient returned to collegiate athletics without any complications. While the most common biologic complications include pretibial cysts, granuloma formation, tunnel widening, and inflammatory reactions, infection is exceedingly rare. Late infection and osteomyelitis are also rare but can occur and should be considered in the differential diagnosis.